The uniform convergence of the values of differential games - Vilkas, E.; Jačiauskas, I. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Й. Вилкас. И. П. Ячяускас. Равномерная сходимость значений дифференциальных игр E. Vilkas, I. Jačiauskas. Diferencialinių lošimų reikšmių tolygus konvergavimas